Elevated water temperature impairs gamete production in male narrow-clawed crayfish Pontastacus leptodactylus (Eschscholtz, 1823) - Farhadi Ardavan; Harlıoglu Muzaffer Mustafa (Knowledge and Management of Aquatic Ecosystems, 2018)
Water temperature is one of the major environmental factors affecting the reproductive output of freshwater crayfish. The reproduction of freshwater crayfish only occurs in a limited water temperature range and minor changes in water temperature could have negative impacts on this biological process. Therefore, understanding the potential effects of temperature on the reproductive output of crayfish is important from both an ecological and aquaculture point of view. Spermatozoal production, hepatosomatic index (HSI), gonado-somatic index (GSI), testicular index (TI), and vas deferens index (VDI) were measured in Pontastacus leptodactylus maintained at 7.5, 11, and 19 °C during the reproductive season. It was found that the highest temperature significantly degrades the production of spermatozoa and VDI when compared to the crayfish maintained at lower temperatures (P < 0.05). On the other hand, water temperature did not significantly affect the values of HSI, GSI, and TI (P > 0.05). Furthermore, the highest temperature caused a negative impact on the vas deferens characterized by a softer and more adhesive texture. In conclusion, this study demonstrated that elevated water temperature has a negative impact on gamete production of male P. leptodactylus, as a cold water crayfish species, and may subsequently affect the whole reproduction process.